Reason and revolution : Hegel and the rise of social theory - "Marcuse, Herbert" (London, 1977)
Marcuse's classic work first published in this country in 1941. Its first part is a survey of the structure of Hegel's system, elucidating those implications of Hegel's ideas that identify them closely with later developments in European thought, particularly after Marx. The second section surveys the post-Hegelian rise of social theory.
Keywords: "Philosophy, Western"